Cupping therapy on low back pain. A systematic review - Rulewska, Natalia Maria; Grabowski, Filip; Michalak, Klaudia; Janowski, Kacper; Neska, Dagmara (Quality in Sport, 2025)
Low back pain (LBP) encompasses a range of symptoms such as discomfort, muscle tension, tenderness, and stiffness in the area between the lower rib cage and the buttocks. The causes of LBP can be divided into two primary categories: specific low back pain, which has identifiable sources, and non-specific low back pain (NSLBP), which lacks a clear cause. Studies indicate that most patients will experience at least one recurrence of LBP within the span of a year. Additionally, around 5 to 10 percent of acute low back pain cases can progress to chronic low back pain (CLBP). Interestingly, around 90% of LBP instances are not associated with identifiable physical anomalies. This poses a significant challenge for healthcare systems, especially considering the persistent and often unclear nature of these pain conditions. To address lower back pain, three common approaches are used: medications, surgical procedures, and rehabilitation programs. In recent years, there has been a growing trend toward complementary and alternative medicine (CAM) in developed countries, largely due to the side effects associated with traditional treatment methods. The aim of this article is to assess the effectiveness of treating low back pain through cupping. A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the searchterms encompassing the following keywords: cupping therapy, low back pain (LBP), chronic back pain, complementary and alternative medicine (CAM). In traditional medicine, treatment methods typically involve options like non-steroidal anti-inflammatory drugs, opioids, muscle relaxants, steroids, and in some cases, surgery. However, emerging research suggests that cupping therapy could be a promising alternative for managing these conditions. To fully understand how long cupping is effective for alleviating lower back pain (LBP), further studies and appropriate follow-ups are essential.